The Dilemma of Local Health Service Policy in the Era of National Health Insurance: A Political Perspective Analysis - Veby Rilian (JURNAL KUASA, 2024)
The strengthening of political priorities in terms of developing health policies for various parties needs to be carried out both for the doctor and for the recipients of health services. Various health policies are influenced by various things based on certain contextual factors. In the Minister of Health Number 59 of 2014, it is stated that the amount of capitation funds is for first-level dental health services in independent practices, but it is not stated how much the capitation rate is for dental health services at community health centers. This research uses quantitative descriptive methods. The calculation method used is the Activity-Based Costing (ABC) method. The results of this study show that the average unit cost of dental health services at the Community Health Center is IDR. 104714. The largest unit cost is the GIC patching action. By using the activity-based cost calculation method, it can be seen that the largest costs for dental health services at the Community Health Center come from employee costs. And this shows that the situation is not fair for various parties. This raises a dilemma that is important to be discussed. The capitation rates set by the government are considered inappropriate for dentists in first-level health facilities. This can cause a decrease in the quality of health services provided by dentists at community health centers.